Opcja preferencyjna na rzecz rodziny odpowiedzią Kościoła w Polsce na postępujący proces sekularyzacji - Fiałkowski, Marek (Verbum Vitae, 2024)
The article asks how the Church can respond to the challenge of secularisation and counter its effects. At the same time, it is assumed that secularisation is not an inevitable phenomenon that one must surrender to by adapting to the current situation. Still, it is possible to develop an appropriate response to this phenomenon. The most appropriate response is prioritising the pastoral care of marriage and family. To this end, an analysis of the Church’s teaching and theological studies was carried out to show their potential, expressed primarily in the sacrament of marriage and the phenomenon of domestic Church. The Church’s strategy in the face of secularisation processes should be focused on discovering the richness of the sacrament of marriage and supporting families in the complex process of becoming a domestic Church. Other pastoral activities of the Church should be adapted and focused on this strategy, because by strengthening the family as the domestic Church, they become more effective.